Comparing the short-term clinical efficacy and nutritional status of Kamikawa and double-tract reconstruction in laparoscopic proximal gastric cancer surgery - Haicheng Yang; Zhuo Han; Ying Yang; Jiaxing He; Bo Zhang; Shuai Zhou; Tao Wu; Qing Qiao; Xianli He; Nan Wang (Asian Journal of Surgery)
Purpose: The purpose of this study was to compare the short-term efficacy and nutritional status of Kamikawa and double-tract reconstruction (DTR) after proximal gastrectomy. Methods: A total of 112 Ⅰ-Ⅱa gastric cancer patients who underwent laparoscopic proximal gastrectomy from June 2020 to January 2024 were enrolled, including 32 patients in the Kamikawa group and 80 patients in the DTR group. The clinical characteristics, outcomes of surgery, postoperative complications and the nutrition indicators (Hb, total protein, albumin and NIR) were collected retrospectively. Results: The average follow-up time was (6.64 ± 1.26) months. Compared with the DTR group, the operation and anastomosis times of the Kamikawa group were longer but had less blood loss and shorter hospital stays. However, there were no significant difference in postoperative first flatus time, first feeding time, the number of lymph nodes removed, lymph nodes dissection time and total hospitalization costs between the two groups. The Kamikawa group showed better nutritional recovery ability and lower reflux ratio of upper gastrointestinal radiography than the DTR group. The incidence of postoperative complications in the Kamikawa group was lower than the DTR group. Conclusion: Although Kamikawa takes slightly longer and requires higher technical skills from the surgical team, it has better postoperative anti-reflux effects and faster postoperative nutritional recovery.